Price Earning Ratio Perusahaan Industri Pertambangan Batubara - Indah Purnama Sari; Rita Martini (Politeknik Negeri Sriwijaya, 2020)
This research is aimed to determine whether the effect of current ratio, debt to equity ratio,and return on assets to price earnings ratio on the Coal Mining Industry Company. Population used amounts 21 companies. Samples were obtained amounts 14 companies using purposive sampling method of sample selection. Hypothesis tests used are f test, t test, and the coefficient of determination.The results showed that variable current ratio, debt to equity ratio, and return on assets have a significant effect to price earning ratio simultaneously. Debt to equity ratio and return on assets have a significant effect to price earning ratio. While current ratio have no effect to price earnings ratio partially.